Evaluation of chemotherapy response between Paclitaxel-Cisplatin, Paclitaxel -Gemcitabine and Gemcitabine - Cisplatin among non - resectable lung cancer patients, A retrospective study in tertiary care hospital. (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Background: To compare the survival rate of paclitaxel plus cisplatin (PC arm), paclitaxel plus gemcitabine (PG arm) and gemcitabine plus cisplatin (GC arm) in chemotherapy patients with non resectable lung cancer.Methods: This was a retrospective observational study to evaluate chemotherapy response among non resectable lung cancer patients with their survival at cancer center CMH, Dhaka since 01 July 2013 to 31 March 2015. One hundred fifty-four (154) non resectable lung cancer patients were randomly divided into three groups, 50 patients in PC arm, 51 patients in PG arm and 53 patients in GC arm. In PC arm paclitaxel 175 mg/m2 (day 1) with cisplatin 75mg/m2 (day 1), in PG arm Paclitaxel 175 mg/m2 (day 1) with gemcitabine 1000 mg/m2 (days 1 and 8) and in GC arm gemcitabine 1000 mg/m2 (days 1 and 8) with cisplatin 100mg/m2 (day 1).Results: Patients characteristics were similar between the three groups. The overall response rate was 40% in the PC arm,43.1% in the PG arm, 43.4% in the GC arm. The median survival time in PC arm was 8.5 months, in PG arm was 8.8 months, in GC arm was 9.2 months. The major side effect was myelosuppression which accounts 71% patients. The average treatment costs were 57% and 30% lower in PC arm as compared with GC and PG arm respectively.Conclusion: The median survival time, disease free survival time and 1-year survival rate in PC, PG, GC arms without significant difference. Treatment were well tolerable; quality of life parameter was mostly similar but paclitaxel with cisplatin was most cost effective than others chemotherapy regimen.J Bangladesh Coll Phys Surg 2020; 38(4): 172-175